The majority of long non-stop reading frames on the antisense strand can be explained by biased codon usage. - Silke, J. (Gene, 1997)
In recent studies it has been suggested that long reading frames on the antisense strand of open reading frames (ORFs) are more frequent than expected. The vertebrate DNA database was searched for long (greater than 900 bp) antisense non-stop reading frames (aNRFs) that overlap known coding regions. The sequences obtained were predominantly positioned in DNA with a high usage of G or C in the third codon position of the sense ORF. The major class of sequences revealed by the search was that of the heat-shock protein 70 kDa (Hsp70) family. A long Hsp70 aNRF was found in many Hsp70 sequences and occurred in species as diverse as fish, flies, fungi and bacteria. The role of codon usage bias was analysed both in the specific case of the Hsp70 genes and in a general species-wide context. The data obtained showed that even the very long aNRFs present in the Hsp70 family could be explained by codon usage bias on the sense strand. Codon usage bias is determined by GC content at the third codon position of the sense ORF and, in some species, by a high expression level of the gene in question. Such an explanation for the occurrence of long aNRFs cannot exclude that some aNRFs are transcribed and translated.